Winnieâ€™s personality in Natalie Babbitâ€™s tuck everlasting a scientific publication - Rizkhan, Aulia (Universitas Ahmad Dahlan, 2020)
This research is entitledâ€ Winnieâ€™s Personality In Natalie Babbitâ€™s Tuck Everlasting.â€ The object of this study is to see the personalities of the character in the novel. This research is based on the awareness psychological approach to the type study and laws of psychology are applied to literary works. In this research, the researcher applied psychological approach and Individual psychological theory. Through the objective approach the researcher see the personalities of the character in the novel. The method of the research is descriptive qualitative method. The main data are taken from words, phrases, and sentences of the novel. The supporting data are taken from some books, articles, and internet. The results of this study are clearly explained as follows. The researcher found six personalities in the novel: fictional finalism, social interest, inferiority feeling, striving superiority, style of life, and creative power. From the six analysis of Adlerâ€™s individual psychological is connected to each other and builds a unity from the main characterâ€™s personality.